Pncagenesequence analysis for pyrazinamide resistance in mycobacterium tuberculosis from High-incidence setting - VAISHALI R WABALE,; AMEETA A JOSHI,; MUTHURAJ MUTHAIAH,; ABHAY S CHOWDHARY, (International Journal of Pharma and Bio Sciences, 2016)
Standard culture-based drug susceptibility testing (DST) of Mycobacterium tuberculosis (MTB) to pyrazinamide (PZA) is difficult to perform. PZA is a prodrug that has to be converted to its active form pyrazinoic acid (POA) by pyrazinamidase (PZase) enzyme, encoded by pncA gene and loss of PZase activity is associated with PZA resistance. To further define genetic basis of PZA resistance and determine the frequency of PZA-resistant strains having pncA mutations. A 100 MTB isolates were examined for PZA susceptibility and analyzed. MTB were identified by phenotypic & genotypic methods. pncA genes from these strains were amplified. Mutations in the sequences of pncA genes from PZA-resistant strains were identified by comparison with wild-type MTB gene sequence using CLC protein workbench version 5.0 software. The frequency of mutations and amino acid changes in the target pncA gene were analyzed. Phylogenetic analysis was performed to know the strain variation among the drug resistant population. 34 among 100 had pncA mutations including nucleotide substitutions (missense mutations), insertions (64.7%) and small deletions (nonsense mutations) (29.4%), causing amino acid substitutions in most cases; frame shifts leading to nonsense polypeptides (5.9%). Identified mutations found dispersed along pncA gene, but some degree of clustering of mutations observed in Pro38Leu, Ile16Ser, Val150Ala and Asp97Asx regions. PCR based sequencing assay targeting pncA mutations, can reliably detect PZA resistance in Multi Drug Resistant (MDR) and rules out PZA resistance in non-MDR MTB isolates. Molecular assays are probably the way forward for detecting PZA resistance.